1993
DOI: 10.1101/gad.7.7a.1229
|View full text |Cite
|
Sign up to set email alerts
|

Genetic investigation of cAMP-dependent protein kinase function in Drosophila development.

Abstract: The cAMP-dependent protein kinase (PKA) has been shown to mediate the vast majority of cellular responses to the intracellular second messenger, cAMP, in eukaryotes. To study the role of cAMP signal transduction in Drosophila development, we have isolated and molecularly characterized mutations of varying severity in the Drosophila PKA gene, DC0. Biochemical measurements indicate that DC0 is either the sole or the major PKA catalytic subunit gene in Drosophila. Adult females heterozygous for a strong and a wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 41 publications
(62 reference statements)
6
124
0
Order By: Relevance
“…All DCO alleles assayed in this article, DC0 B3 , DC0 H2 , DC0 H3 , DCO B10 , and DC0 B12 , are homozygous-lethal, and PKA assays of head extracts of heterozygotes of all 5 alleles show a reduction of PKA activity to Ϸ50% of wild-type activity as assayed biochemically from crude extracts (20,24). However, previous studies have revealed notable differences between these different alleles.…”
Section: A General Reduction In Pkac Activity Is Responsible For the mentioning
confidence: 73%
See 3 more Smart Citations
“…All DCO alleles assayed in this article, DC0 B3 , DC0 H2 , DC0 H3 , DCO B10 , and DC0 B12 , are homozygous-lethal, and PKA assays of head extracts of heterozygotes of all 5 alleles show a reduction of PKA activity to Ϸ50% of wild-type activity as assayed biochemically from crude extracts (20,24). However, previous studies have revealed notable differences between these different alleles.…”
Section: A General Reduction In Pkac Activity Is Responsible For the mentioning
confidence: 73%
“…In a previous study, we determined that heterozygotes of lethal point mutations in DC0, the gene encoding the major catalytic subunit of cAMP-dependent protein kinase (PKAc), dramatically delay AMI onset (20). These heterozygotes all reduce PKA activity to Ϸ50% of wild type and delay AMI onset Ͼ2-fold (20,24). While characterizing these mutants further, we made the startling observation that some of them also improve memory retention in young flies.…”
Section: Identification Of Specific Point Mutations That Improve Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Antisera against the following proteins were used: bovine VATPase subunit A and subunit E (Roussa et al, 1998), Culex quinquefasciatus V-ATPase subunit B (Filippova et al, 1998), Manduca sexta V-ATPase subunits d, C and D (Merzendorfer et al, 2000;Tiburcy et al, 2013) and Drosophila melanogaster PKA catalytic subunit and regulatory subunit II (Lane and Kalderon, 1993;Skoulakis et al, 1993). Cross-reactivity of these antibodies with the homologous proteins in C. vicina has been demonstrated previously (Zimmermann et al, 2003;Dames et al, 2006;Voss et al, 2007;Voss et al, 2009;Baumann and Walz, 2012).…”
Section: Reagentsmentioning
confidence: 99%